Provincial corruption, corporate accrual quality, and corporate earnings manipulation: Evidence from an emerging country - Thi Huong Giang Vuong (Cogent Business & Management)
Based on the unique setting of the administrative decentralization context and local corruption issues in Vietnam, this paper aims to provide empirical evidence of the impact of provincial corruption on corporate accrual quality (CAQ) and corporate earnings manipulation (CEM) from 2010 to 2022. I apply fixed-effect models to examine the effect of provincial corruption on the quality of corporate accruals in Vietnam, as well as the role of foreign block-holders in this effect. The findings show that CAQ is better in low-corrupt provinces. Deep analyses impose that provincial corruption has a stronger detrimental impact on discretionary CAQ than on innate CAQ. Additionally, enterprises operating in high-corruption provinces engage more in income-decreasing earnings manipulation practices than their counterparts in low-corruption provinces. Furthermore, the effect of provincial corruption on corporate accrual quality and earnings manipulation is insignificant in enterprises with the subsistence of foreign block-holders. The findings deliver critical notes to the company’s stakeholders regarding the usefulness of accounting information in the condition of listed firms operating locally with severe corruption in Vietnam. This study adds to the body of literature on the effects of local corruption at the business level in a developing economy.